NORM Technique based PAPR Reduction in MC-CDMA Systems - Noor Mohammed Vali Mohamad; P. S Mallick; L. Nithyanandan; Srujan Dharmagadda; M. Surendrakumar; M. Palanivelan (Journal of ICT Research and Applications, 2015)
Multicarrier code division multiple access (MC-CDMA) is one of the promising technologies for future-generation wireless networks. It offers high data rates, protection against frequency-selective fading and efficient utilization of the spectrum. The peak to average power ratio (PAPR) is very high in MCCDMA systems. The partial transmit sequence technique (PTS) and the selective mapping technique (SLM) reduce the PAPR with more computational complexity. In this study, the NORM technique was used for PAPR reduction in MC-CDMA systems. The performance of NORM was analyzed with PTS and SLM in terms of cumulative complementary distribution, power saving gain, amplifier efficiency, computational complexity and bit error rate. Simulation results showed that NORM has better PAPR reduction with less computational complexity.